Features of Students’ Economic Competence Formation - Komelina, Valentina A.; Mirzagalyamova, Zulfiya N.; Gabbasova, Lyaisan B.; Rod, Yuliya S.; Slobodyan, Malika L.; Esipova, Svetlana A.; Lavrentiev, Sergei Y.; Kharisova, Guzyal M. (International Review of Management and Marketing, 2016)
The paper provides the verification of a proposed technique aimed to develop students’ economic competence and considers criteria of students’ economic competence formation: motivational that is characterized by personality’s qualities and properties, tolerance and psychological readiness for future profession; cognitive that identifies the level of economic literacy development, assimilation of knowledge, mastering a complex of concepts, categories, laws; activity-based that assumes mastering actions that have an economic focus; abilities of rational labour organization; use of knowledge in non-standard situations; realization of design, organizational and implementation skills necessary for economic activity. On the basis of proposed criteria the authors revealed problems in the levels of students’ economic competence formation, and the technique was elaborated to enrich cognitive, motivational and activity-based components that feature the degree of experts’ readiness for vocational activity. Materials from the article can be useful for teachers of economic disciplines to select and structure the training content for students specializing in economic disciplines. Keywords: economic competences, students, economic specialties, technique. JEL Classifications: A2; A20; I2; I25